2020
DOI: 10.1177/2156759x20904501
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based School Counseling: Expanding the Existing Paradigm

Abstract: This special edition of Professional School Counseling provides some of the key proceedings from the seventh annual Evidence-based School Counseling Conference (EBSCC). As the conceptual and practical aspects of conducting evidence-based school counseling (EBSC) have evolved, those changes are reflected in the conference content. This article identifies some of the ways that EBSC has progressed, including making sure that multiple aspects of student well-being—such as mental health and social-emotional learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 25 publications
0
36
0
Order By: Relevance
“…Placing the ecological intersection of identities of students among the multiple ecological systems students navigate daily (McMahon et al, 2014) reinforces the exploration of inequities inherent in K–12 systems while uncovering the individual needs of students (Dimmitt & Zyromski, 2020). The result is that the data reflecting students’ needs drives both the delivery system of the school counseling program and the leadership and advocacy efforts of the school counselor.…”
Section: Using Data-based Decision Making To Prioritize Students’ Dev...mentioning
confidence: 95%
“…Placing the ecological intersection of identities of students among the multiple ecological systems students navigate daily (McMahon et al, 2014) reinforces the exploration of inequities inherent in K–12 systems while uncovering the individual needs of students (Dimmitt & Zyromski, 2020). The result is that the data reflecting students’ needs drives both the delivery system of the school counseling program and the leadership and advocacy efforts of the school counselor.…”
Section: Using Data-based Decision Making To Prioritize Students’ Dev...mentioning
confidence: 95%
“…How a person uses the term evidence-based practice, or, in this case, evidence-based school counseling, is important. In a recent article (Dimmitt & Zyromski, 2020), we suggested that interpreting the construct of EBSC as the search for evidence-based interventions is limiting. Evidence-based interventions often reflect manualized programs that can be helpful when addressing an identified student-level issue, as long as that intervention has been validated with similar populations (see Mason and Trezek [2020] for a useful guide for this process).…”
Section: Understanding Ebsc As a Series Of Opportunities For Creating...mentioning
confidence: 99%
“…The first author was a school counselor for Grades 4–6 with 18 years of experience in the same district. Over the years, she had intentionally established an evidence-based school counseling program grounded in an ecological model (Dimmitt & Zyromski, 2020; McMahon et al, 2014). She worked collaboratively across all levels of the interlocking systems—centering children while drawing from educators, leaders, families, and community members—to recognize and appreciate the values, yearnings, inequities, and strengths in her school.…”
Section: Case Study In Elementary Advocacymentioning
confidence: 99%
“…In the latest iteration of evidence-based school counseling, school counseling scholars advise that mental health and social/emotional needs require the same data-driven processes that school counselors have in place to meet students’ academic needs (Zyromski et al, 2021). As with other student challenges, when addressing student mental health, school counselors are encouraged to recognize the identities of students who are disproportionately affected and explore the conditions that foster inequity in access to school mental health services (Dimmitt & Zyromski, 2020; Zyromski et al, 2021). When encountering such inequities, school counselors can then apply data-driven approaches to advocate for underrepresented students (Dimmitt, 2018; Zyromski & Mariani, 2016).…”
mentioning
confidence: 99%